REMOVAL EFFICIENCY OF NITROGEN, PHOSPHORUS AND HEAVY METALS ASSOCIATED WITH SWINE WASTEWATER USING AQUATIC MACROPHYTES - Nguyen, Chung Tan; Nguyen, Ha Van (BIOTROPIA, 2023)
Wastes from breeding farms have globally increased greenhouse gas emissions and caused serious pollution of aquatic environments. Biogas treatment polymer bags could significantly reduce organic compounds; however, they could not effectively treat other pollutants in animal wastewater. The objective of this study was to assess the removal efficiency of salinity and pollutants associated with pig wastewater using aquatic macrophytes. Four macrophytes, namely Acrotichum aureum, Eleocharis dulcis, Typha domengensis, and Limnophyton obtusifolium, and a soil control without vegetation were randomly assigned into fifteen mesocosms (1.2 × 0.7 × 0.6 m) with three replicates for each treatment. Pig wastewater was continuously filled into the input chambers of the mesocosms every three days at a volume of 5 liters. Water samples were collected from the output chambers at 60 and 120 days after treatment, while soil and vegetation samples were collected at the beginning and at the end of the experiment. The results showed that E. dulcis, T. domengensis, and L. obtusifolium were dominant in the removal of N, P, Cu, Zn, and suspended solids; E. dulcis and T. domengensis significantly increased dissolved oxygen; whereas the treatment with L. obtusifolium showed the best efficiency in salt-ion removal. Pollutants of N, P, Cu, and Zn tended to accumulate more in macrophyte roots than in their leaves. Accumulation of N, P, Cu, and Zn in L. obtusifolium biomass was the highest compared with other treatments. From these findings, it is suggested that a combination of three aquatic macrophytes, including E. dulcis, T. domengensis, and L. obtusifolium, could establish a constructed wetland system to directly treat pollutants in livestock wastewater.